Beyond AI: Sosialisasi Dampak Sosial Kecerdasan Artifisial Dan Literasi Digital Siswa SMA Negeri 4 Kota Bengkulu - Dewantara, Ramadhan; Kartika, Shofi Dwi; Havizah, Nurul; Putri, Fhariska Dhia; Ariant, Ririn Dwi; Jumadi, Juju (Universitas Dehasen Bengkulu, 2026)
The rapid development of Artificial Intelligence (AI) necessitates digital literacy that transcends technical skills, focusing instead on its social and ethical implications. This community service program, titled